2007
DOI: 10.1111/j.1365-2923.2007.02791.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between senior medical students' and pharmacy pre-registrants' knowledge and perceptions of generic medicines

Abstract: Although there were some differences in responses, both groups had knowledge deficits about the quality, safety and effectiveness of generic medicines, which need to be addressed by educators in order to increase the future use of generic medicines in Australia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
54
6
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 21 publications
9
54
6
1
Order By: Relevance
“…[13] High proportion of medical students pointed that they do not need more information on conducting bioequivalence tests. This was in contrast with the reports by Das and Das and Hassali et al [14,11] but it may reflect misunderstanding of medical students about the importance of such courses. On the other hand, pharmacy students were eager to accept more information when it was offered to them; especially, when a topic was more related to pharmacy curriculum.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…[13] High proportion of medical students pointed that they do not need more information on conducting bioequivalence tests. This was in contrast with the reports by Das and Das and Hassali et al [14,11] but it may reflect misunderstanding of medical students about the importance of such courses. On the other hand, pharmacy students were eager to accept more information when it was offered to them; especially, when a topic was more related to pharmacy curriculum.…”
Section: Discussioncontrasting
confidence: 79%
“…The result in this study agreed with the finding reported by previous studies. [11][12] Moreover, Siam et al reported that there was a significant difference among pharmacy and medical students regarding knowledge of generic medicine in Bangladesh. [4] In contrast, a study conducted by Basak and Sathyanarayana in India showed that many of the pharmacists and drug retailers have misconception regarding generic medicines, and they lack enough knowledge about generic substitution, even if the prescribed medicines are not available.…”
Section: Discussionmentioning
confidence: 99%
“…The median number of students per study was 104 (range 1–2413). Besides final‐year medical students, some studies also involved 1–5th year students ( n = 20) 24, 25, 26, 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, junior doctors and residents ( n = 8) 25, 28, 33, 46, 47, 48, 49, 50, medical specialists ( n = 2) 48, 50, pharmacy students ( n = 3) 32, 51, 52, dental students ( n = 2) 31, 41 and nonhealthcare students ( n = 1) 40.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies showed that students generally had poor knowledge of, and negative perceptions about, prescribing generic medicines 46, 51, 84. They were generally under the misapprehension that generic medicines were inferior in quality, less effective and produced more side effects than brand‐name medicines 46, 51, 84.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation